Laryngeal Mask Airway Clinical Use and Training: A Survey of North American Neonatal Health Care Professionals - Robin, Beverley; Soghier, Lamia M.; Vachharajani, Akshaya; Moussa, Ahmed (American Journal of Perinatology, 2023)
Objective The aim of this study was to explore North American neonatal health care professionals' (HCPs) experience, confidence, skill, and training with the laryngeal mask airway (LMA).Study Design This was a cross-sectional survey.Results The survey was completed by 2,159 HCPs from Canada and the United States. Seventy nine percent had no clinical experience with the LMA, and less than 20% considered the LMA an alternative to endotracheal intubation (EI). The majority had received LMA training; however, 28% of registered nurses, 18% of respiratory therapists, 17% of physicians, and 12% of midwives had never inserted an LMA in a mannequin. Less than a quarter of respondents agreed that the current biennial Neonatal Resuscitation Program instruction paradigm is sufficient for LMA training. All groups reported low confidence and skill with LMA insertion, and compared with all other groups, the respiratory therapists had the highest reported confidence and skill.Conclusion This survey study, which is the first of its kind to include midwives, demonstrates that neonatal HCPs lack experience, confidence, skill, and training with the LMA, rarely use the device, and in general, do not consider the LMA as an alternative to EI. These findings contribute to, and support the findings of previous smaller studies, and in conjunction with the diminishing opportunities for EI, highlight the need for programs to emphasize the importance of the LMA for neonatal airway management and prioritize regular LMA training, with focus that parallels the importance placed on the skills of EI and mask ventilation.Key Points
Keywords: LMA; survey; North American; neonatal health care professionals; neonatal resuscitation